KARAKTERISASI TEPUNG BUMBU BERBASIS MOCAF (MODIFIED CASSAVA FLOUR) DENGAN PENAMBAHAN MAIZENA DAN TEPUNG BERAS - Muhammad Afifudin Anwar; Wiwik Siti Windrati; Nurud Diniyah (JURNAL AGROTEKNOLOGI, 2016)
Spice flour is one of the ready-made products are produced from a mixture of flour and seasoning. The base material used are MOCAF (Modified Cassava Flour), cornstarch, rice flour and food additive or seasoning. The aims of this study are to determine influence of the addition of cornstarch and rice flour on the spice flour from MOCAF and its application on fried tempeh products and the addition of cornstarch and rice flour from effectiveness test from physical and chemical characteristics and the application in the spice flour products fried tempeh. Design experimental that used to this study was using Complete Randomized Design (CRD) one factor. The formulas i.e. MOCAF with 50% concentration added cornstarch (30%, 25%, 20%, 15% and 10%) and rice flour (10%, 15%, 20%, 25% and 30%) and spice flour were used to. The result show is a the best formulation consisted of fried tempeh products and spice flour using MOCAF 50%, cornstarch 30 % and rice flour 10% with characteristic of viscosity 8.05 mp; WHC 90.93%; OHC 109.77%; ash content 6.06%; protein content 1.80%; and starch content 81.67%. The characteristic of fried tempeh result in lightness (L*) 57.82; adhesiveness 48.78%; moisture content 14.99% and fat content 30.11%. in sensory evaluation the most acceptable colour of fried tempeh was 3.88 (heading like), aroma 3.84 (heading like), 3.68 (heading like), favorite texture 3.32 (kinda like) and overall 3.68 (heading like). Keywords: Spice flour, MOCAF, cornstarch, rice flour